Integrating the Gutzeit method with X-Ray fluorescence spectroscopy for rapid quantification of inorganic arsenic in selected beverages. (March 2021) - Zhang, Zhiyun; Lin, Helen; Ma, Chuanxin; Zhang, Lingzi; Zelevinsky, Julia; Xia, Ming; Xu, Yuecheng; White, Jason C.; Tyson, Julian; He, Lili
Abstract: Inorganic arsenic (iAs) in foods has raised significant concerns because it is carcinogenic to human beings. Herein, we integrated the Gutzeit method with X-ray fluorescence (XRF) spectroscopy to measure iAs in selected beverages within 45 min. Briefly, iAs was firstly reduced to arsine under acidic conditions. Transformed arsine was then trapped on mercury bromide test discs and subsequently measured by XRF. Interference from dimethylarsinate on the test discs was minimized by an acetone rinsing step to a great extent. A standard curve with a linear range from 0 to 133.3 μg/L was established, and the limit of detection and quantification were 1.9 and 5.7 μg/L, respectively. This method was further evaluated with commercial beverages, and the results were compared with those from a commercial arsenic test kit and by inductively coupled plasma mass spectroscopy. We demonstrated that this method is sensitive, reliable, fast, and comparatively cost-effective for use in iAs screening in the food industry. Highlights: Gutzeit method coupled with XRF was used to detect inorganic arsenic in beverages. The LOD and LOQ of this developed method are 1.9 μg/L and 5.7 μg/L, respectively. Dimethylarsinate interference on test discs could be minimized by acetone wash.